Access to digital and social media among Romanian HIV/AIDS clinical providers - Carmen Manciuc; Brooke A. Levandowski; Erin Muir; Amanda Radulescu; Monica Barbosu; Timothy D. Dye (Taylor & Francis Group, 2018)
The WHO/UNAIDS suggests that digital tools - such as social media and online training opportunities, can connect providers in difficult social and medical contexts to providers elsewhere for guidance, support, and advice. Social media is emerging as an innovative option for connecting clinicians together and for enhancing access to professional resources. In Romania, characterized by an atypical HIV/AIDS epidemic which is further challenged by a range of access complexities, it is unclear how often - and which kinds of - social media clinicians use to support clinical care. This study was conducted to ascertain social media use for clinical providers based in two regions of Romania (Transylvania and Moldavia) who face distance challenges that could potentially be alleviated by social media interaction. We used an online survey to understand what social media are currently popular and perceived to be useful for learning clinical information. Descriptive and bivariate analyses were conducted. Providers indicated Facebook and WhatsApp were the most common social media platforms, with 62% and 45% reporting daily use, respectively. Providers who used one media platform were significantly more likely to use another social media platform (p < .05). These data are helpful for creating an online training platform on HIV/AIDS for Romanian clinical providers.